Chalcogen Chemistry - Papoh Ndibewu, Peter (IntechOpen, 2019)
This is a handy textbook comprised of chapters introducing the fundamentals of chalcogen chemistry with a focus on chalcogens and selected derived compounds and/or materials with illustrative practical applications. These low-valent chemistry elements of Group 16 or group VI- in the modern periodic table include oxygen (O), sulfur (S), selenium (Se), tellurium (Te), and polonium (Po), and they exhibit extremely interesting properties. They are endowed with supramolecular and structure bonding reactivities that allow them to form a variety of new compounds with sophisticated characteristics, thus making their way into a new era of materials development. It is hoped that readers of this textbook with a general background knowledge in chemistry, biogeochemistry, biochemistry, biology, food, agriculture, and also medicine, as well as pharmacy, will find the chapters enriching in new knowledge. An introductory chapter orients readership in this particular field of chemistry with a summative focus on the multidisciplinary approach employed in the compilation of the chapters. As such, the text is suitable for scientists, technologists, students, as well as those whose major interest is chalcogen chemistry, with particular interests in the chalcogen compounds and materials.